2006
DOI: 10.1111/j.1468-2419.2006.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Construct validation of an Arabic version of the Learning Transfer System Inventory for use in Jordan

Abstract: The purpose of this study was to translate and validate an Arabic version of the Learning Transfer System Inventory (LTSI) for use in Jordan. The study also investigated the perceptions of transfer system characteristics across selected individual and situational variables. The LTSI was administered to 450 employees of 28 different public and private sector organizations operating in Jordan. Principal axis factoring with oblique rotation was used to uncover the underlying structure of the Arabic version of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 22 publications
2
61
1
2
Order By: Relevance
“…Trainers can use the results of learner responses to the LTSI to identify areas that may impair positive training transfer at the learner, design, and work climate levels. While the bulk of empirical work using the LTSI has been to validate the instrument with domestic and international samples (Khasawneh, Bates, & Holton, 2004;Yamnill & McLean, 2005) and to conduct correlational studies involving learner and organizational variables (Bates & Khasawneh, 2005;Seyler et al, 1998), there has been no published work linking the use of the LTSI to actual improvement in transfer outcomes.…”
Section: Needs Analysismentioning
confidence: 99%
“…Trainers can use the results of learner responses to the LTSI to identify areas that may impair positive training transfer at the learner, design, and work climate levels. While the bulk of empirical work using the LTSI has been to validate the instrument with domestic and international samples (Khasawneh, Bates, & Holton, 2004;Yamnill & McLean, 2005) and to conduct correlational studies involving learner and organizational variables (Bates & Khasawneh, 2005;Seyler et al, 1998), there has been no published work linking the use of the LTSI to actual improvement in transfer outcomes.…”
Section: Needs Analysismentioning
confidence: 99%
“…In the light of his results, Al-Taani emphasized the necessity of involving participants in identifying their own training needs, and in planning their own training programs. Khasawneh (2004) established the relationship between the learning transfer system domain and the organizational learning domain, thus expanding their homological network. Learning transfer systems explained a significant portion of the total variance in each measure of organizational learning.…”
mentioning
confidence: 99%
“…Tracey, Tannenbaum, and Kanavagh (1995) stress that administrative practices and careful planning influence transfer. However, the lack of cohesiveness between the designing and delivering of training hinders learning transfer (Bookter, 1999;Khasawneh, 2004). Although environmental and administrative factors are important for transfer, Holton and Baldwin (2000) indicate that personal factors also determine the effectiveness of transfer, such as motivation and prior experience of trainees.…”
Section: Background and Literature Reviewmentioning
confidence: 97%
“…Several studies validated the LTSI and concluded that the instrument is a comprehensive, valid, empirically based, cross-culturally tested, and diagnostic measure to assess learning transfer (Bates, 2001;Chen et al, 2005;Khasawneh, Bates, & Holton, 2006). After validating the instrument inside the United States, researchers validated the LTSI in several foreign countries (see, for example, Chen, 2003;Khasawneh, 2004;Khasawneh et al, 2006).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation